Genetic Diversity of Nitrogen-Fixing and Plant Growth Promoting Pseudomonas Species Isolated from Sugarcane Rhizosphere - Li, Hai-Bi; Singh, Rajesh K.; Singh, Pratiksha; Song, Qi-Qi; Xing, Yong-Xiu; Yang, Li-Tao; Li, Yang-Rui (Frontiers in Microbiology, 2017)
The study was designed to isolate and characterize Pseudomonas spp. from sugarcane rhizosphere, and to evaluate their plant- growth- promoting (PGP) traits and nitrogenase activity. A biological nitrogen-fixing microbe has great potential to replace chemical fertilizers and be used as a targeted biofertilizer in a plant. A total of 100 isolates from sugarcane rhizosphere, belonging to different species, were isolated; from these, 30 isolates were selected on the basis of preliminary screening, for in vitro antagonistic activities against sugarcane pathogens and for various PGP traits, as well as nitrogenase activity. The production of IAA varied from 312.07 to 13.12 μg mL-1 in tryptophan supplemented medium, with higher production in AN15 and lower in CN20 strain. The estimation of ACC deaminase activity, strains CY4 and BA2 produced maximum and minimum activity of 77.0 and 15.13 μmoL mg-1 h-1. For nitrogenase activity among the studied strains, CoA6 fixed higher and AY1 fixed lower in amounts (108.30 and 6.16 μmoL C2H2 h-1 mL-1). All the strains were identified on the basis of 16S rRNA gene sequencing, and the phylogenetic diversity of the strains was analyzed. The results identified all strains as being similar to Pseudomonas spp. Polymerase chain reaction (PCR) amplification of nifH and antibiotic genes was suggestive that the amplified strains had the capability to fix nitrogen and possessed biocontrol activities. Genotypic comparisons of the strains were determined by BOX, ERIC, and REP PCR profile analysis. Out of all the screened isolates, CY4 (Pseudomonas koreensis) and CN11 (Pseudomonas entomophila) showed the most prominent PGP traits, as well as nitrogenase activity. Therefore, only these two strains were selected for further studies; Biolog profiling; colonization through green fluorescent protein (GFP)-tagged bacteria; and nifH gene expression using quantitative real-time polymerase chain reaction (qRT-PCR) analysis. The Biolog phenotypic profiling, which comprised utilization of C and N sources, and tolerance to osmolytes and pH, revealed the metabolic versatility of the selected strains. The colonization ability of the selected strains was evaluated by genetically tagging them with a constitutively expressing GFP-pPROBE-pTetr-OT plasmid. qRT-PCR results showed that both strains had the ability to express the nifH gene at 90